Nanomedicine developments in the treatment of metastatic pancreatic cancer: focus on nanoliposomal irinotecan - Ko AH (Dove Medical Press, 2016)
Andrew H KoDivision of Hematology/Oncology, Helen Diller Family Comprehensive Cancer Center, University of California, San Francisco, San Francisco, CA, USA Abstract: Nanoliposomal irinotecan (nal-IRI) was originally developed using an efficient and high-loading capacity system to encapsulate irinotecan within a liposomal carrier, producing a therapeutic agent with improved biodistribution and pharmacokinetic characteristics compared to free drug. Specifically, administration of nal-IRI results in prolonged exposure of SN-38, the active metabolite of irinotecan, within tumors, while at the same time offering the advantage of less systemic toxicity than traditional irinotecan. These favorable properties of nal-IRI, confirmed in a variety of tumor xenograft models, led to its clinical evaluation in a number of disease indications for which camptothecins have proven activity, including in colorectal, gastric, and pancreatic cancers. The culmination of these clinical trials was the NAPOLI-1 (Nanoliposomal irinotecan with fluorouracil and folinic acid in metastatic pancreatic cancer after previous gemcitabine-based therapy) trial, an international Phase III study evaluating nal-IRI both alone and in combination with 5-fluorouracil and leucovorin in patients with metastatic pancreatic adenocarcinoma following progression on gemcitabine-based chemotherapy. Positive results from NAPOLI-1 led to approval of nal-IRI (with 5-fluorouracil/leucovorin) in October 2015 by the US Food and Drug Administration specifically for the treatment of metastatic pancreatic cancer in the second-line setting and beyond, a clinical context in which there had previously been no accepted standard of care. As such, nal-IRI represents an important landmark in cancer drug development, and potentially ushers in a new era where a greater number of patients with advanced pancreatic cancer can be sequenced through multiple lines of therapy translating into meaningful improvements in survival.Keywords: pancreatic cancer, irinotecan, nanoliposomal, clinical trial, NAPOLI-1